Comparison of Japanese encephalitis virus (JEV) growth in C6/36 and vero cell lines - Jarnis, Floriece Ellniss (Universiti Malaysia Sarawak (UNIMAS), 2015)
Japanese Encephalitis (JE) is a single-stranded positive sense RNA virus belongs to the family Flaviviridae and genus flavivirus. It has been one of the major causative agents of viral encephalitis in Southest Asia. The main objective of this study was to compare the growth of JEV in two different cell lines which are the C6/36 and Vero cell lines. In this study the comparison were done by looking at the differences of days of cytopathic effect (CPE) occurred, the titer of the virus harvested from each of the cell line by plaque assay and the differences in the RNA concentration extracted from each of the cell line by RT-PCR. For the purpose of this study, different strains of JEV as well as different methods of plaque assay were used. The final results obtained show that there were significant differences between growing JEV in C6/36 and Vero cell lines.